Legacy Phosphorus After 45 Years With Consistent Cropping Systems and Fertilization Compared to Native Soils - Zhang, T. Q.; Zheng, Z. M.; Drury, Craig F.; Hu, Q. C.; Tan, C. S. (Frontiers in Earth Science, 2020)
Agricultural practices affect the status of legacy phosphorus (P) in soils and consequently the P bioavailability and susceptibility of losses to water resources. Previous studies have primarily assessed P status within agro-ecosystems and rarely have these results been compared to virgin conditions. We evaluated the effects of long-term (45 years) consistent cropping (continuous corn, CC; corn-oats-alfalfa-alfalfa rotation, CR,; and continuous bluegrass sod, CB) with and without P fertilization on changes in P fractions of different bioavailability in a Brookston clay loam, as compared to an adjacent virgin forest. Soil P was separated into various inorganic P (Pi) and organic P (Po) fractions using a modified sequential fractionation method. Phosphorus in virgin soil was predominated by moderately labile Po (NaOH-Po), 44%, followed by moderately stable Pi (HCl-P), 26%. Compared to the virgin soil, consistent cropping without P fertilization significantly decreased all P fractions except for water extractable Po, with the largest decrease in labile Pi (water-Pi + NaHCO3-Pi) and moderately labile Po of 65 and 73 mg kg-1, respectively, over 45 years. Consistent cropping with fertilization retained comparable amount of total P in CC and RC, but increased total P in CB, relative to the virgin soil. Averaged over cropping systems, labile Pi, NaOH-Pi, and HCl-P increased by 129, 74 and 20 mg kg-1, respectively, whereas, labile Po and moderately labile Po decreased by 8 and 60 mg kg-1, respectively, compared to the virgin soil. This study indicates that long-term cropping significantly enhanced the rate of moderately labile Po mineralization, irrespective of fertilization. The increased total P and Po in the fertilized CB plots suggests that P accumulation in long-term grass fields is a concern as far as potential P contamination in surface waters.